Socialization of Fishing Boat Safety Standards and Procedures for Fishermen at PPI Beba, Takalar Regency - Djafar, Wihdat; Djalante, Abd. Haris; Chairunnisa, A. Sitti; Idrus, Misliah; Clausthaldi, Fadhil Rizki; Asri, Syamsul; Ardianti, Andi; Asis, Muhammad Akbar; Wahyuddin, Wahyuddin; Fitrah, Rifkah (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Fishing activities by fishermen in Indonesia have high-risk characteristics known as 3D: dangerous, dirty, and challenging. This Community Service (PkM) activity aims to increase fishermen's knowledge at the Beba Fish Landing Base (PPI), Takalar Regency, regarding safety standards and procedures for fishing boat shipping. Through outreach activities, fishermen are provided information on safety equipment, shipping safety procedures, work safety, and occupational health. The socialization method uses brochure media with an interactive approach for each individual, including pre-test, delivery of material, and post-test to evaluate increased knowledge. The survey results showed that before the socialization, the level of fishermen's knowledge was deficient, with only 13% – 39% of the 23 fishermen understanding safety standards. After socialization, there was a significant increase of 57% – 74% of fishermen showed better understanding (increased 35% – 43%). Based on the results of this PkM activity, ongoing outreach needs to be carried out to increase awareness and implement safety procedures among fishermen to reduce the risk of accidents at sea.